Behind the Image - The Image Behind : on covering and incovering media : Artefact Festival. - STUK Kunstencentrum, Leuven (Leuven : STUK Kunstencentrum Leuven, 2009)
Kocken, Gert Jan ; Simon, Taryn ; Schaber, Ines ; Zmijewski, Artur ; Farocki, Harun ; D'Haeseleer, Kurt ; Maire, Julien ; Capurro, Christian ; Linz, Pia ; Andersson, Christian ; Popp, Julius ; Ohanian, Melik ; Lucas, Kristin ; Bismarck, Julius von ; Luxemburg Sebastian, Robert ; Weibel, Peter ; Phiffer, Dan ; Zer-Aviv, Mushon ; Nolen, David ; Reble, Jürgen ; Köner, Thomas ; Engels, Ludo ; Champ d'Action ; Voigt, Wolfgang ; Crew
Engels en Nederlands
Exhibition. Artefact Festival : Behind the image - the image behind. Leuven. STUK Kunstencentrum Leuven, 10.02.2009 - 15.02.2009
boek